Penguatan Tata Kelola BUMKam Narey melalui Pemutakhiran Data Retribusi dan Sosialisasi di Kampung Sereh, Distrik Sentani, Kabupaten Jayapura (Lembaga Pengembangan Kinerja Dosen, 2026)
This community service article reports the results of two integrated community service programs (Kuliah Kerja Nyata) conducted by Student Group 15 of Universitas Cenderawasih in Kampung Sereh, Sentani District, Jayapura Regency: (1) a household data-collection program on public cemetery retribution and clean water services, and (2) a socialization event introducing BUMKam (village-owned enterprise) governance, both centered on BUMKam Narey. Methods included field observation, direct interviews with heads of household, structured data-collection forms, verification with RT/RW leaders, and a participatory outreach event involving village officials, the BUMKam director, and an external resource person. Data were collected from 92 households. Results show that only 24% of households had recorded cemetery retribution data, with recorded amounts ranging widely from IDR 250,000 to IDR 10,000,000; the most frequent amount was IDR 5,000,000 for adults and IDR 2,000,000 for children. For clean water, 24 households used piped municipal water (PAM), 33 paid for village-managed water, 33 used village water without payment, and most households that expressed a tariff preference favored IDR 20,000 per month.